Walking Poetics of the Bumba Meu Boi from Maranhão:: the brincante scene in the feast of São Marçal - Souza, Danielle (Revista Brasileira de Estudos da Presença, 2023)
This text examines the action of walking as an inventive practice and its probable experimentation in the feast of São Marçal in São Luís, Maranhão. To do so, the research focuses on the moving poetics produced by the Bumba Meu Boi groups that present the sensitive occurrences and aesthetic specificities of the feast of São Marçal, in relation to other June festivities in the state. Additionally, it addresses the brincante body, considering its festive and walking expressiveness as a possible state of creation, and highlights an inventive poetics, alive and living in the spiral temporality that generates collective exchanges and walking experiments in the investigated event.